Proceedings of the 9th ACM Workshop on Mobility in the Evolving Internet Architecture 2014
DOI: 10.1145/2645892.2645901
|View full text |Cite
|
Sign up to set email alerts
|

ParaDrop

Abstract: The landscape of computing capabilities within the home has seen a recent shift from persistent desktops to mobile platforms, which has led to the use of the cloud as the primary computing platform implemented by developers today. However, a growing number of high quality services restrict computational tasks to be colocated with the enduser. Thus, we introduce a specific edge computing framework, called ParaDrop, which allows developers to leverage one of the last bastions of persistent computing resources in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…By reviewing the existing literature, Bonomi et al in [31] suggested edge devices to be configured as either virtualized (in VMs) or offered as bare metal. However, other contributions, see [47], [48] and [49], use the containers to run applications in fog nodes -considered in these works as mini-clouds at the edge of the network -, due to their reduced memory capacity, computing footprint, and small size. Aligned to the latter concepts, if the mini-cloud component in the fog node is virtualized by means of containers, shall we assume that edge devices should be virtualized in the same fashion?…”
Section: Edge Device Virtualizationmentioning
confidence: 99%
“…By reviewing the existing literature, Bonomi et al in [31] suggested edge devices to be configured as either virtualized (in VMs) or offered as bare metal. However, other contributions, see [47], [48] and [49], use the containers to run applications in fog nodes -considered in these works as mini-clouds at the edge of the network -, due to their reduced memory capacity, computing footprint, and small size. Aligned to the latter concepts, if the mini-cloud component in the fog node is virtualized by means of containers, shall we assume that edge devices should be virtualized in the same fashion?…”
Section: Edge Device Virtualizationmentioning
confidence: 99%